ASSESSING MEASUREMENT MODEL OF MALAYSIAN VOLUNTARY SAVING DECISION FOR FUTURE RETIREMENT USING CONFIRMATORY FACTOR ANALYSIS - Julaina Baistaman; Zainudin Awang; Rabihah Nawawi; Noorfadzilah Arifin; Wan Masnieza Wan Mustapha; Asma Syazwani Shari (International Journal of Accounting, Finance and Business, 2020)
Advancement in healthcare and improvement in quality of life has significantly increase longevity of Malaysians. Unfortunately, Malaysian generally does not financially prepare for their future retirement. Insufficient saving for retirement among Malaysian to sustain retirement life becomes huge concern nowadays. Fewer past studies had been done to access voluntary saving decision among Malaysian working adult as this study aims to provide insight of factual findings for decision making and policy implementation. In order to solve the problem, we need to identify the indicators in order to measure voluntary saving behaviour and acting further steps to be taken to improve the behavior. This study was conducted to develop a scale to measure voluntary saving decision and testing the validation of the measurement using Confirmatory Factor Analysis (CFA). This study need to validate the measurement model of voluntary saving decision for its unidimensionality, validity, reliability and fitness indexes for model fitness. The result reveals that the measurement model of voluntary saving decision had achieved the requirement for construct validity and successfully developed which suitable to be used in future of research.